Revista sobre la biodiversidad y el ecoturismo de las Cavernas de Jumandy, en el Cantón Archidona en la Provincia de Napo-Tena - Bauz Rosas, Andrea Carolina (2015)
The following document contains a theorical and practical research about the biodiversity and ecotourism in "Las cavernas de Jumandy en Archidona" triying to achieve a level of awareness and own conscience about the environment. The results about the research are all detailed in a well developed magazine, with collected information from different sources, such as the local authorities, local residents and as well from tourists. The research starts with a visit throughout the inside and outside of the caverns, showing the wildlife that this site has; including the concepts and definitions of the archetypes that we found there. As the ecotourism is part of this research we also considered other factors, like the conservation of the caverns and their environment. This project contains and reveals the background and the different demonstrations in the traditional, gastronomical and mythological area , enclosed in these caverns. It Is also important to show and demonstrate the responsible ecotourism that we can -obtain from tourists , as well as maintaining the social memory about how this place have been evolving to become a part of the history of our country. Allowing us to reassure the identity of the Ruku Jumandy Kawsay community, who are responsible for the care and maintenance of the site. To finish, our research concludes with a communicative product that includes different articles, photo galleries and interviews that denote how the ecotourism works inside the Jumandy Cavern.